Curcumin for depression: a meta-analysis. Issue 15 (21st August 2020) - Fusar-Poli, Laura; Vozza, Lucia; Gabbiadini, Alberto; Vanella, Antonio; Concas, Ilaria; Tinacci, Silvia; Petralia, Antonino; Signorelli, Maria Salvina; Aguglia, Eugenio
Abstract: Curcumin is the principal curcuminoid found in turmeric ( Curcuma longa ), a spice frequently used in Asian countries. Given its anti-inflammatory and antioxidant properties, it has been hypothesized that curcumin might be effective in treating symptoms of a variety of neuropsychiatric disorders, such as depression. We conducted a systematic review following the PRISMA guidelines. In August 2019, we screened 930 articles, of which 9 were eligible for the meta-analysis. In 7 articles, participants were affected by major depressive disorder (MDD), while in other two they suffered from depression secondary to a medical condition. We found an overall significant effect of curcumin on depressive (10 studies, 531 participants, Hedge's g  = −0.75, 95% CI −1.11 to −0.39, p  < 0.001) and anxiety symptoms (5 studies, 284 participants, Hedge's g = −2.62, 95% CI −4.06 to −1.17, p  < 0.001), with large effect size. Curcumin was generally well-tolerated by patients. Our findings suggest that curcumin, if added to standard care, might improve depressive and anxiety symptoms in people with depression. However, given the small sample size, our results should be cautiously interpreted. Further trials should be implemented, particularly in Western countries, where curcumin does not represent a usual component of dietary regimens.